POLA RUANG EKONOMI DI KAWASAN PINGGIRAN PERKOTAAN - Eppy Yuliani; Mila Karmilah; M. Agung Ridlo (Jurnal Planologi, 2021)
ABSTRACTThe development of the center of the city of Semarang is very rapid, leading to the outskirts. The outskirts, which were originally used as agricultural areas, have now been converted into built-up areas, settlements, trade and services. This research was conducted in Tembalang Village, which is an educational area, new settlements accompanied by the growth of economic activity. The purpose of this study is to find patterns of economic space in suburban urban areas. Methodology Descriptive analysis research using a qualitative and rationalistic deductive approach that focuses on the environmental approach (behavior approach) and the spatial economic approach. From the results of the analysis, it is concluded that Tembalang Village has an Economic Spatial Pattern that develops along the main road. Economic activities that follow this main road route form a network pattern. This pattern of economic space is also still visible in the surrounding area. The pattern of economic space that develops on the main road corridor has a high selling value of land. Every year there is an increase in land prices, both according to NJOP, land rental prices and land selling prices.Keywords: pattern, space, economy, activity, suburbs, urban. ABSTRAKPerkembangan pusat Kota Semarang yang sangat pesat, mengarah pada kawasan pinggiran. Kawasan pinggiran yang awalnya sebagai  fungsi kawasan  pertanian, banyak beralih fungsi menjadi kawasan terbangun, pemrmukiman, perdagangan dan jasa. Penelitian ini dilakukan di Kelurahan Tembalang, yang merupakan kawasan pendidikan, permukiman baru disertai dengan pertumbuhan aktivitas ekonomi. Tujuan penelitian ini menemukan pola ruang ekonomi pada kawasan pinggiran perkotaan. Metodologi Penelitian analisis deskriptif dengan menggunakan pendekatan deduktif Kualitatif Rasionalistik yang berfokus pada pendekatan lingkungan (behaviour approach) dan pendekatan ekonomi keruangan (spatial economic approach). Dari hasil analisis disimpulkan Kelurahan Tembalang memiliki Pola Ruang Ekonomi yang berkembang di sepanjang jalan utama. Kegiatan perekonomian yang mengikuti jalur jalan utama ini mementuk pola jaringan. Pola ruang ekonomi ini juga masih terlihat pada kawasan sekitarnya. Pola ruang ekonomi yang berkembang pada koridor  jalan utama, memiliki nilai jual lahan yang tinggi. Semakin tahun mengalami kenaikan harga lahan baik menurut NJOP, harga sewa lahan maupun harga jual lahan.Kata kunci : pola,ruang, ekonomi, aktivitas, pinggiran, perkotaan.